Capturing Plastic Surgery on Film—Making Reconstruction Visible. Issue 9 (September 2017) - Lunger, Alexander; Ismail, Tarek; Sarraf, Namita; Epple, Christian; Schaefer, Kristin Marit; Schaefer, Dirk J.
Abstract : Summary: The Swiss Plastic Surgery Association (https://plasticsurgery.ch/en/ ) decided to produce a corporate video to illustrate the concept of "plastic surgery of confidence" to the public. We show the diversity of specializations and the vast range of tasks that surgeons passionately handle day in and day out. We wanted to convey 2 main messages: first, that plastic surgery is more than just cosmetic surgery, and second, that plastic surgery in Switzerland is synonymous with quality and confidence. We selected 17 topics that we felt had good filmic potential and would best explain to the public what plastic surgery is about. This included the selection of appropriate patients, experts, and locations from all over the country. We thought it crucial to show the initial preoperative situation, as only in this case would the achievement of reconstruction be evident and comprehensive to the layman audience. The actual production was filmed in 5 different locations and took 5 days of shooting. We recorded 17 surgeons, 9 patients, and about 30 voluntary background actors. From 23 hours of footage, we created a 7 minute, 22 second corporate video, recorded in 3 of the Swiss national languages. The video was presented to the public online in June 2016, on the same day as the National Open Day of Plastic Surgery in Switzerland. The video is available online. We evaluated the impact of the video using a questionnaire for lay people and observed that it could substantially improve the perception of our specialty, especially regarding the reconstructive aspect. We feel that a freely available corporate video is a very useful means to promote plastic surgery and help patients better understand what it is all about.